Beyond Ostrom: Randomized experiment of the impact of individualized tree rights on forest management in Ethiopia - Ryo Takahashi; Keijiro Otsuka; Mesfin Tilahun; Emiru Birhane; Stein Terje Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2021)
In this study, we argue that while community forest management is effective in protecting forest resources as argued by Ostrom, it may fail to provide proper incentives to take care of such resources because of collective sharing of benefits of forest management. This study proposes a mixed private and community management system as a desirable arrangement for timber forest management in Ethiopia, which is characterized by communal protection of communityowned forest area and individual management of individually owned trees. By conducting a randomized experiment in Ethiopia, we found that the mixed management system significantly stimulated intensive forest management activities, including pruning, guarding, and watering. Furthermore, the treated members extracted more timber trees and forest products, which are byproducts of tree management (thinned trees and pruned branches). In contrast, the extracted volumes of nontimber forest products unrelated to tree management (fodder and honey) did not change by the intervention.
Keywords: O13; Q23; Q24; P48; 330; property regimes; individual rights; commons; community forest management; RCT